New blood in contemporary cinema : women directors and the poetics of horror - Pisters, Patricia (Edinburgh University Press Ltd, 2020)
The book investigates contemporary women directors who put 'a poetics of horror' to new use in their work, expanding the range of gendered and racialized perspectives in the horror genre.